Emergence of Ancient Ceramics in East Asia (the Geoarcheological Aspect). Issue 1 (3rd April 2019) - Kuz'min, Yaroslav V.
Abstract : The emergence of pottery in East Asia manifests in the early Neolithic, occurring during the Late Glacial [ranging 15, 000–10, 000 radiocarbon years ago (BP)], in three regions: 1) the Japanese Islands; 2) the Amur River basin; and 3) Southern China. As ceramics from these three centers are quite different, they probably appeared in these regions independently yet approximately at the same time, c. 14, 000–13, 000 [years] BP (c. 17, 000–14, 500 calendar years ago). This is the oldest pottery in the Old World found so far. Earlier dates from several Neolithic sites in southern China, Xianrendong, Miaoyan, and Yuchanyan (c. 15, 000 [years] BP) need to be confirmed. Using radiocarbon and paleoenvironmental data, it has been established that pottery-making technology appeared before the rapid and sharp climatic changes of the Late Glacial, such as the Older Dryas cooling and the Bølling warming. The general natural background for the emergence of pottery in East Asia was a gradual warming and an increase of broadleaved tree species, with abundant nut and seed resources. The earliest ceramic vessels in Japan and the Amur River basin were used mainly for cooking vegetable and meat foods, and possibly for processing fish.